A Method for Determining the Kinetics of Small-Molecule-Induced Ubiquitination. (April 2021) - Vieux, Ellen F.; Agafonov, Roman V.; Emerson, Lydia; Isasa, Marta; Deibler, Richard W.; Simard, Jeffrey R.; Cocozziello, David; Ladd, Brendon; Lee, Linda; Li, Heng; Archer, Stephen; Fitzgerald, Mark; et al.
Recent advances in targeted protein degradation have enabled chemical hijacking of the ubiquitin–proteasome system to treat disease. The catalytic rate of cereblon (CRBN)-dependent bifunctional degradation activating compounds (BiDAC), which recruit CRBN to a chosen target protein, resulting in its ubiquitination and proteasomal degradation, is an important parameter to consider during the drug discovery process. In this work, an in vitro system was developed to measure the kinetics of BRD4 bromodomain 1 (BD1) ubiquitination by fitting an essential activator kinetic model to these data. The affinities between BiDACs, BD1, and CRBN in the binary complex, ternary complex, and full ubiquitination complex were characterized. Together, this work provides a new tool for understanding and optimizing the catalytic and thermodynamic properties of BiDACs.